School Resource Management for Literacy Success: A Managerial Perspective on the Gajahkeris Program - Jati, Ratih Pramudya; Soedjono, S Soedjono; Violinda, Q. Qristin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to examine the implementation of the Gajahkeris Literacy Program against four key variables: communication, resources, stakeholder disposition, and bureaucratic structure. The program was developed as a strategic response to strengthen student literacy through structured routines and stakeholder collaboration within the Merdeka Belajar framework. Using a qualitative case study approach, data were collected through interviews, observation, and documentation. Data analysis employed a systematic and literate approach, including thematic coding, the Edward III framework, and key variables (communication, resources, disposition, structure) to assess the implementation of the Gajahkeris Program. The study findings indicate that effective teacher-student communication, strong leadership, and the use of creative learning materials positively contribute to student literacy engagement. However, challenges arise in the form of inconsistent parental involvement, limited feedback mechanisms, and bureaucratic rigidity that hinder responsive decision-making. This study provides implications regarding the importance of strengthening the communication framework between teachers, students, and parents, as well as the need for increased professional development to support program implementation. Furthermore, improvements in the feedback system and bureaucratic flexibility are needed to ensure responsive and effective decision-making.